2020
DOI: 10.1007/s00453-020-00681-y
|View full text |Cite
|
Sign up to set email alerts
|

Parameterized Complexity of Conflict-Free Matchings and Paths

Abstract: An input to a conflict-free variant of a classical problem Γ, called Conflict-Free Γ, consists of an instance I of Γ coupled with a graph H, called the conflict graph. A solution to Conflict-Free Γ in (I, H) is a solution to I in Γ, which is also an independent set in H. In this paper, we study conflict-free variants of Maximum Matching and Shortest Path, which we call Conflict-Free Matching (CF-Matching) and Conflict-Free Shortest Path (CF-SP), respectively. We show that both CF-Matching and CF-SP are W[1]-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
53
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(54 citation statements)
references
References 30 publications
(24 reference statements)
0
53
1
Order By: Relevance
“…There is a long history of study on treewidth and parameterization on treewidth [3,4,6]. For a wide range of hard problems, algorithms with running time of the form f (k) • n O (1) exist if the input graph comes with a tree decomposition of width k. Moreover, in many cases, we have good understanding of the best possible form of f (k) in the running time (under suitable complexity assumptions, such as the Exponential Time Hypothesis (ETH) or the Strong Exponential Time Hypothesis (SETH) put forward by Impagliazzo and Paturi [25]). Marx et al [32] studied the B-Factor problem for this viewpoint, parameterized by treewidth for finite, fixed lists B.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…There is a long history of study on treewidth and parameterization on treewidth [3,4,6]. For a wide range of hard problems, algorithms with running time of the form f (k) • n O (1) exist if the input graph comes with a tree decomposition of width k. Moreover, in many cases, we have good understanding of the best possible form of f (k) in the running time (under suitable complexity assumptions, such as the Exponential Time Hypothesis (ETH) or the Strong Exponential Time Hypothesis (SETH) put forward by Impagliazzo and Paturi [25]). Marx et al [32] studied the B-Factor problem for this viewpoint, parameterized by treewidth for finite, fixed lists B.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that a combination of standard dynamic programming techniques with fast subset convolution (cf. [38]) give a (max B + 1) tw n O (1) time algorithm for the decision, minimization, maximization, and counting versions. Furthermore, this form of running time is essentially optimal conditioned on the SETH.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations